Developing Variations of Classroom Management-Based Learning Models in Junior High School - Ahmad Zarkasyi (Ashfiya Journal of Qualitative Insight in Islamic Studies, 2026)
This article aims to describe the preparation a teacher must undertake to develop a learning method using a classroom management approach at 2 Bustanul Ulum Dawuhan Lumajang Junior High School. This research employed a qualitative case study approach. Data collection included observation, interviews, and documentation. Source triangulation was used to validate the data. The results showed that teacher preparation for learning included varied seating arrangements, such as traditional, semicircular/U-shaped, and group seating. Teachers alternated student seating arrangements. The learning methods developed included: a) the student role-playing learning method developed by the teacher, which was able to arouse enthusiasm and increase learning enthusiasm. b) The expert group method was able to foster students’ courage to express their opinions in class. c) The investigative method was able to foster good work habits in everyday life.